Comparative cohort study of volumetric modulated arc therapy for squamous cell cancer of unknown primary in the head and neck—Involved neck only versus mucosal irradiation. (17th September 2020) - Poon, Wai‐Yan; Thomson, Maureen; McLoone, Philip; Wilson, Christina; Crosbie, Robin; Schipani, Stefano; Grose, Derek; James, Allan; Lamb, Carolynn; Rizwanullah, Mohammed; Campbell, Frances; Easton, Fiona; et al.
Abstract: Objectives: Target volumes for irradiation remain ill‐defined for squamous cell cancer of unknown primary in the head and neck (SCCUP). The aim of this study was to compare involved neck only (INO) radiotherapy (RT) with irradiating involved neck plus potential mucosal primary sites and contralateral neck (MUC) in patients diagnosed and treated with modern diagnostics and techniques. Design: This is a retrospective cohort study. Patients with a diagnosis of SCCUP with unilateral neck disease were included. Results: Thirty patients were identified. All underwent FDG PET‐CT. 47% of patients had HPV‐positive SCC. 20 patients received RT to INO, 10 patients to MUC, all with volumetric modulated arc therapy (VMAT). A significantly lower dose for each organ at risk was delivered in INO‐treated patients, with mean dose to contralateral parotid gland 57% less. The proportion of patients with late grade 2 or worse xerostomia was higher in MUC patients. The incidence of grade 2‐3 mucositis (89% vs 45%) and grade 3 or worse dysphagia (50% vs 10%) was higher in MUC patients. Median follow‐up was 31 months. No mucosal primaries emerged. Progression‐free survival at 2 years was 74.7% for INO patients, 70% in the MUC group. Overall survival at 2 years was 79.7% in the INO group and 70% in the MUC patients. Conclusion: INO radiotherapy for patients with SCCUP of the head and neck is a safe treatment strategy resulting in clinically significant lower RT doses to OARS. Acute and late toxicities are reduced without detriment to patient survival.